1997
DOI: 10.1111/j.1745-6584.1997.tb00172.x
|View full text |Cite
|
Sign up to set email alerts
|

EPM Modeling of a Field‐Scale Tritium Tracer Experiment in Fractured, Weathered Shale

Abstract: A 2D equivalent porous media (EPM) model was used to simulate transport of tritium for a field‐scale tracer experiment in a fractured and highly weathered shale saprolite. The tritium plume was characterized by rapid migration of the leading edge of the plume (up to 0.4 m/day), slower movement of the center of mass of the tritium pulse (0.009 m/day) and very slow decline of concentrations in the “tail” of the breakthrough curve (which has persisted at the site for at least 16 years). The EPM model successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Additional field tracer experiments, that involved adding solutes or colloids to wells in the deeper shale/ siltstone saprolite at Burial Ground 4 (Webster, 1996;McKay et al, 1997) and at West Bear Creek Valley McKay et al, 2000) and monitoring their down-slope movement, showed that once infiltration reached the water table, which typically occurs just above the saprolite-bedrock contact, it could also move very rapidly (b1 to 200 m/day). Both the stormflow zone and the upper portion of the water table zone (especially where it includes the saprolitebedrock transition zone) are considered as potential rapid contaminant migration pathways at the ORR.…”
Section: Introduction and Review Of Previous Sedimentary Rock Saprolimentioning
confidence: 98%
See 1 more Smart Citation
“…Additional field tracer experiments, that involved adding solutes or colloids to wells in the deeper shale/ siltstone saprolite at Burial Ground 4 (Webster, 1996;McKay et al, 1997) and at West Bear Creek Valley McKay et al, 2000) and monitoring their down-slope movement, showed that once infiltration reached the water table, which typically occurs just above the saprolite-bedrock contact, it could also move very rapidly (b1 to 200 m/day). Both the stormflow zone and the upper portion of the water table zone (especially where it includes the saprolitebedrock transition zone) are considered as potential rapid contaminant migration pathways at the ORR.…”
Section: Introduction and Review Of Previous Sedimentary Rock Saprolimentioning
confidence: 98%
“…The weathered material overlying the shale and siltstone is typically 1 to 10 m thick and retains a substantial amount of sedimentary layering and structure from the parent bedrock: Hence, it is referred to as saprolite (Dreier et al, 1987;Hatcher et al, 1992;Driese et al, 2001). Field studies in shale or siltstone saprolite at ORR include: pedologic and geologic characterization (Rothschild et al, 1984a,b;Dreier et al, 1987;Dorsch and Katsube, 1999;Driese et al, 2001); measurement of hydraulic properties of the solumn and upper C-horizon (Luxmoore et al, 1981b;Watson and Luxmoore, 1986;Wilson and Luxmoore, 1988;Wilson et al, 1989); lateral flow and transport of solute tracers in the upper 1-2 m of the solumn and saprolite (Wilson et al, 1993); vertical infiltration and solute transport in a 3 m deep undisturbed pedon (Jardine, personal communication); solute or colloid tracer experiments in the saturated zone just above the saprolite-bedrock contact Webster, 1996;Sanford et al, 1996;McKay et al, 1997McKay et al, , 2000; tracer experiments or monitoring of contaminant plumes in the partially weathered rock just below the saprolitebedrock contact (Olsen et al, 1983;Shevenell et al, 1994;McCarthy et al, 1998a,b;Jardine et al, 1999;Lenczewski et al, 2003).…”
Section: Introduction and Review Of Previous Sedimentary Rock Saprolimentioning
confidence: 98%
“…Jørgensen et al (, ), McKay et al (), Helmke et al (), and Chambon et al (), among others, have shown that numerical models based on different conceptual models of transport in fractures can all be calibrated to reproduce equally well‐observed contaminant distributions in a porous medium that contains fractures or macropores. It can therefore be argued that the choice of a conceptual model to simulate transport in fractured porous media is mainly a question of preference or practicability, providing that transport in fractures and other macropores is accounted for (Helmke et al ; Harrar et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Conditions that favor the suitability of the EPM and DP models are uniform and high macropore density compared to the scale of investigation, and rapid contaminant diffusion into the matrix blocks relative to advection along the fractures (Sudicky 1990;Jørgensen et al 1998;Helmke et al 2005). Jørgensen et al (1998Jørgensen et al ( , 2004a, McKay et al (1997), Helmke et al (2005), and Chambon et al (2011), among others, have shown that numerical models based on different conceptual models of transport in fractures can all be calibrated to reproduce equally well-observed contaminant distributions in a porous medium that contains fractures or macropores. It can therefore be argued that the choice of a conceptual model to simulate transport in fractured porous media is mainly a question of preference or practicability, providing that transport in fractures and other macropores is accounted for (Helmke et al 2005;Harrar et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Preferential flow has been a subject of increasing interest particularly in contaminant hydrology. Investigations have shown that fractures and macropores provide shortcuts for the contaminant and significantly affect the hydraulic, dispersive, and hydrochemical characteristics of the porous medium [Keller et al, 1986;DMstous et al, 1989;JOrgensen and Fredericia, 1992;McKay et al, 1997;Villholth et al, 1998].…”
Section: Introductionmentioning
confidence: 99%